2014
DOI: 10.1111/petr.12421
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography, laboratory, and cholangiography correlation of biliary complications in pediatric liver transplantation

Abstract: The aim of this study is to correlate the US, laboratory, and cholangiography findings in pediatric liver transplant patients with biliary complications, trying to identify reliable decision-making tools for the management of these complications. Retrospective review was carried out of US results in 39 consecutive patients, from 2011 to 2013, with biliary complications after LT, documented by PTC. According to US biliary dilation, patients were classified as: mild, moderate, and severe, and according to labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The development of intrahepatic bile duct dilatation may take several months before being detectable on US when a significant anastomotic stricture occurs. 4,18,[22][23][24][25][26][27] In children after LT, Feier et al demonstrated that 70% of the patients with BS had normal US findings, 7 in agreement with our results where 45% of the patients had normal US, with a PPV of 87% but very low sensitivity (57.1%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The development of intrahepatic bile duct dilatation may take several months before being detectable on US when a significant anastomotic stricture occurs. 4,18,[22][23][24][25][26][27] In children after LT, Feier et al demonstrated that 70% of the patients with BS had normal US findings, 7 in agreement with our results where 45% of the patients had normal US, with a PPV of 87% but very low sensitivity (57.1%).…”
Section: Discussionsupporting
confidence: 92%
“…The accuracy of ultrasound (US) to make the diagnosis of BS varies widely in the literature and ranges from 25% to 95%. The development of intrahepatic bile duct dilatation may take several months before being detectable on US when a significant anastomotic stricture occurs 4,18,22‐27 …”
Section: Discussionmentioning
confidence: 99%
“…Second, an episode of biopsy‐related cholangitis should trigger definitive evaluation for occult biliary stricture, either with endoscopic retrograde cholangiography or percutaneous transhepatic cholangiogram and biliary drainage. This recommendation is supported both by our data and by previous studies that describe the low sensitivity and specificity of liver tests, ultrasound examination, magnetic cholangiopancreatography (MRCP), and even liver biopsy to diagnose biliary stricture . These studies reveal a much lower sensitivity and specificity of both ultrasound and MRCP in detecting biliary strictures in patients with bilioenteric anastomoses instead of duct to duct, which is very commonly the case in children …”
Section: Discussionsupporting
confidence: 85%
“…Regarding complications, biliary complications were the ones most frequently observed in LSG and RSG. Currently, these complications are routinely managed using percutaneous or endoscopic procedures both in pediatric and in adult LT and are therefore considered to be treatable and transient …”
Section: Discussionmentioning
confidence: 99%